Laboratory experiment in psychology - V А Barabanschikov (Peoples' Friendship University of Russia (RUDN University), 2011)
The characteristic of the experimental method in psychology is given. The stages of the making and development, and also the place of the laboratory experiment in modern Russian psychology are considered. The guiding lines and conditions of the technological re-equipment of the machinery of the psychological science in Russia are discussed.